IMPROVING THE SKILLS OF CHOOSING DRUGS USING THE CBIA METHOD IN THE COMMUNITY OF MAJELIS TAKLIM NURUZHOLAM CILEMPUYANG VILLAGE - Muhibatul Lailiah; Yuhansyah Nurfauzi; Mika Tri Kumala Swandari (International Islamic Medicine Forum, 2023)
Housewives are the